Effects of blum’s phase based instruction on the mathematical modelling abilities among year 5 pupils - Harsharanjit Kaur; Kwan Eu Leong (Annals of Mathematical Modeling, 2022)
Skills required by pupils for the 21st century differ from what was required twenty years back. The results of the 21st century concentrates on the abilities and knowledge pupils must learn to be successful in college, life and work. In order to do this, pupils should be taught to master critical thinking skills. The effective way is by including modelling in their syllabus. In mathematics learning, mathematical modelling deals with modelling and application in mathematics teaching, characterising pupils’ modelling abilities and application of modelling activities toward building their competencies. In this study, seventy fifth grade pupils from a school in Selangor, Malaysia, were chosen as the participants. Quantitative approach was used in this study. These pupils were selected using convenience sampling procedure. Open ended tasks based on some real-world problems were given to the pupils. Their answers were assessed using a rubric score table. The scores ranged from 1 to 3 and there was explanation in each score to give marks to their answers. descriptive statistics and Analysis of Covariance (Ancova) were used for answering the research questions. The findings showed that the pupils in the experimental group performed very well in their modelling task whereas pupils in the control group could not perform well in the modelling task.